Amoebic gill infection of turbot, Scophthalmus maximus - Dyková, I.; Figueras, A.; Novoa, B.
Amoebae were found to cause severe gill tissue damage in turbot, Scophthalmus maximus L. from a grow-out facility in northwestern Galicia (Spain). The nature and extent of lesions along with negative results of bacteriological and virological examination made this agent responsible for mortalities in four turbot stocks supplied with water from a single source. We present our findings, although we failed to isolate amoebae, since there was a clear evidence of their primary role in the development of disease condition and occurrence of mortalities. In addition, this is a record both of a new host endangered by amoebae in intensive cultures and pathogenesis of the gill lesions.